Didactic sequence videos to improve English skills through teaching recycling to fifth graders using the CLIL methodology. (2018)
This project proposes to improve students' English language skills for fifth graders, through proposing a learning material that integrates the Content and Language Integrated Learning (CLIL) methodology which allows teaching a subject in a foreign language, for this case it is chosen the content the teaching of the 3 R's of the recycling (reduce, reuse and recycle) of the subject of natural sciences in which it is integrated into the English language.